PENERAPAN HUKUM TERHADAP TINDAK PIDANA MENYAMPAIKAN INFORMASI PALSU YANG MEMBAHAYAKAN PENERBANGAN - Teguh Arif Setiawan; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Aviation Security is a condition that provides protection to aviation from unlawful acts through the integration of the utilization of human resources, facilities, and procedures. One of the threats to the safety and security of aviation is the presence of information that is threatening to safety and security. Threats to the security and safety of civil aviation against acts of terrorism and its derivatives, including information on threats to the safety and security of aviation either verbally, through social media, telephone, mail kites, packages, or otherwise. Threats received by airlines on threats and terror information will be taken seriously to ensure the safety and security of aviation. The purpose of writing this skrisi is; First, to find out how the application of the law to criminal acts conveys false information that endangers aviation. Secondly, to find out how the application of law to perpetrators who claim to jokingly convey false information that endanger the flight.This type of research can be classified in the type of normative juridical research, namely research that discusses the principles of law, legal system, level of legal synchronization, in this case researchers discuss the principles of law. This research is done by examining library materials or secondary data in the form of legislation and books written by legal experts related to research titles, articles, journals and various other sources. The data source used is secondary data source. Secondary data is divided into three types, namely: primary legal materials, secondary legal materials and tertiary legal materials, data collection techniques in this study used literature review method or documentary study.From the results of research problems there are two main things that can be concluded. First, Delivering False Information that jeopardizes flights under the Terrorism Act is called an act of terrorism because it has caused fear of the crowd. Second, the application of the law to the perpetrator conveying false information claiming to joke that endanger the flight may be subject to article 437 paragraph (1) of Law Number 1 of 2009 on Aviation. Until now the application of criminal sanctions Article 437 paragraph (1) Law No. 1 of 2009 on Aviation for perpetrators has not been done. The author's suggestion, Firstly, the Elements of Regulation No. 15 of 2003 on the Eradication of Terrorism Crime and Law Number 1 of 2009 on Aviation to make it more clear that the application of its law can be executed in accordance with the actions of the perpetrator to convey false information that endanger Aviation . Secondly, criminal sanctions for perpetrators passing false information that endangers flights should be more assertive.Keywords: Implementation-False Information